Effective branding begins with a name ... and other keys to creating brands people love - Till, Brian 1960- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from The truth about creating brands people love (ISBN: 9780137128167) by Brian D. Till and Donna Heckler. Get branding right from the start, with great product names, powerful differentiators, and meaningful, motivating, memorable taglines. Good branding starts with the name--the representation of the brand, conjuring images, concepts, and experiences"--Resource description page.
Keywords: Branding (Marketing); Stratégie de marque; branding